Musical identities - Macdonald, Raymond A.R.; Hargreaves, David J.; Miell, Dorothy (Oxford Oxford university press, 2002)
Music is a tremendously powerful channel through which people develop their personal and social identities. Music is used to communicate emotions, thoughts, political statements, social relationships, and physical expressions. But, just as language can mediate the construction and negotiation of developing identities, music can also be a means of communication through which aspects of people's identities are constructed. Music can have a profound influence on our developing sense of identity, our values, and our beliefs, whether from rock music, classical music, or jazz. Different research studies in social and developmental psychology are beginning to chart the various ways in which these processes occur. This is the first book to examine the extraordinary relationship between music and identity from a psychological perspective.